Effects of different smoking temperatures on nutritional values and bacterial contents in corbicula fluminea (Etak) - Bibi Zafirah Zaki (2022)
Corbicula fluminea is a bivalve species that has been a popular snack in Kelantan for generations and is locally known as etak salai. Corbicula fluminea can filter the particles suspended in the water. The method of preparing etak salai practised by the vendors in Kelantan is grilling or smoking it. Raw C. fluminea is marinated using traditional herbs and undergoes a smoking process. The method used to smoke the C. fluminea is very important due to the previous studies showing that the traditional smoking method has no standardisation in terms of time or temperature during the smoking process. Therefore, it is difficult to ensure the bacteria present in C. fluminea tissue can be destroyed which can lead to food-borne disease. This study aims to determine the nutritional values and bacterial contents as well as the best smoking temperature in smoked C. fluminea via modified oven at different smoking temperature. The smoking temperature was set at 75 °C, 85 °C, 95 °C, 100 °C and 105 °C for sample treatment and preparation. The samples were collected from sellers in Pasir Mas and Tumpat in Kelantan, Malaysia. The proximate analysis of C. fluminea samples was analysed according to the Association of Official Analytical Chemists standard method. Then, the mineral element analysis was carried out using wet digestion and identified using Atomic Absorption Spectrophotometry (AAS). Bacterial contents were identified using the most probable number method (MPN). The findings showed that the proximate composition was increased as the temperature increased, the lowest moisture (76.15%), ash (3.20%), crude fat (8.03%), crude protein (8.07%) and carbohydrate (1.52%) were recorded at 105 °C, 85 °C, 95 °C, 85 °C and 85 ºC, respectively and the highest moisture (78.95%), ash (3.52%), crude fat (9.09%), crude protein (8.85%) and carbohydrate (2.66%) were recorded at 85 °C, 95 °C, 105 °C, 105 ºC and 100 ºC, respectively. However, mineral composition was decreased as the temperature increases, the lowest sodium (2931.79 mg/kg), calcium (75.05 mg/kg), magnesium (19.85 mg/kg), iron (18.27 mg/kg), zinc (2.43 mg/kg) and potassium (84.61 mg/kg) were recorded at 85 °C, 85 °C, 85 °C, 100 °C, 100 °C and 100 °C, respectively and the highest sodium (4734.20 mg/kg), calcium (236.42 mg/kg), magnesium (40.76 mg/kg), iron (28.84 mg/kg), zinc (4.27 mg/kg) and potassium (138.96 mg/kg) were recorded at 100 °C, 95 °C, 85 °C, 75 °C, 75 °C and 75 °C, respectively. Regarding bacterial content, there is no bacterial contamination for either total coliform or faecal coliform (E. coli) in C. fluminea detected with temperature ranging from 75 °C to 105 °C. In conclusion, smoking temperatures affected the nutritional values and bacterial contents of C. fluminea. The smoking temperature at 85 °C with a smoking time of 30 minutes and airflow of 1.0 m/s is the appropriate condition for smoking C. fluminea in an oven to maintain the nutritional value and kill all the bacteria in C. fluminea tissue.